Rewriting Colonial Narratives: Intertextuality, Feminism, and Postcolonial Subversion in J.M. Coetzee’s Foe - Regmi, Suresh; Gautam, Shreedhar (International Research Journal of MMC, 2026)
Daniel Defoe’s Robinson Crusoe (1719) is often regarded as a cornerstone of English literature, reinforcing colonial ideology through its narrative of exploration, conquest, and civilization. However, J.M. Coetzee’s Foe (1986) challenges this foundational narrative, using intertextuality, postmodernism, and metafiction to expose the silences and erasures within colonial discourse. This study critically examines Foe through postcolonial and feminist perspectives, drawing on Edward Said’s Orientalism (1978) and Gayatri Spivak’s Can the Subaltern Speak? (1988) to reveal how Coetzee subverts the imperialist and patriarchal assumptions of Defoe’s text. Employing a comparative textual analysis, this research positions Foe within the broader landscape of postcolonial literature and intertextual theory. Through Said’s contrapuntal reading, the study explores how Coetzee deconstructs Defoe’s narrative authority, particularly through the reimagined voices of Susan Barton and Friday. Spivak’s concept of subaltern silence is central to the examination of Friday’s muteness, illustrating how Coetzee critiques the marginalization of colonized subjects in both historical and literary contexts. The findings reveal that Foe is not merely a retelling of Robinson Crusoe but a radical revision that dismantles the myth of the self-sufficient European man while highlighting the epistemic violence imposed on women and indigenous figures. Coetzee’s use of narrative fragmentation, unreliable narration, and metafiction disrupts the traditional colonial framework, emphasizing the instability of historical knowledge. This study argues that Foe serves as a politically charged reconfiguration of literary history, challenging dominant narratives of empire and authorship. By interrogating colonial storytelling and questioning whose voices are heard and whose are erased, Foe becomes a powerful act of literary resistance, creating space for alternative histories that reclaim the voices of the silenced.